2014
DOI: 10.1002/pi.4787
|View full text |Cite
|
Sign up to set email alerts
|

Development of silver nanoparticles-loaded calcium alginate beads embedded in gelatin scaffolds for use as wound dressings

Abstract: Silver nanoparticles (AgNPs)‐loaded calcium alginate beads embedded in gelatin scaffolds were developed to sustain and maintain the release of silver (Ag+) ions over an extended time period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…From these results, it might be concluded that the size of embedded beads affected the compressive modulus of the scaffold. The smaller sizes of the embedded beads and the higher compressive modulus of the scaffolds were obtained according to the structural reinforcement principle …”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…From these results, it might be concluded that the size of embedded beads affected the compressive modulus of the scaffold. The smaller sizes of the embedded beads and the higher compressive modulus of the scaffolds were obtained according to the structural reinforcement principle …”
Section: Resultssupporting
confidence: 88%
“…From the previous study, Pankongadisak et al prepared the neat and nAg‐containing CaAlg beads with the diameter range between ~140 and ~149 µm . Thus, the emulsification/external gelation method was employed in this study to prepare smaller diameters of the neat and nAg‐containing CaAlg beads.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found 11 studies using silver-impregnated dressings that evaluated wound odor, in 10 it was a secondary outcome,1,7,33,51,5355,5759,60 and it was the primary outcome in one clinical case series where silver was used along with activated charcoal 126. The authors reported a reduction in wound malodor and an increase of tissue granulation.…”
Section: Efficacy Of Various Treatments On Wound Odormentioning
confidence: 99%
“…[49][50][51][52] Silver-based wound care dressings contain nano-sized silver particles that signifi cantly enlarge the surface area of the silver and enhance its antimicrobial actions when compared to bulk silver metal. 57 Charged nanoparticles adhere to the bacterial cell wall impairing function of key proteins and enzymes.…”
Section: Silvermentioning
confidence: 99%